Role of Runx2 in Calcific Aortic Valve Disease in Mouse Models - Dharmarajan, Subramanian; Speer, Mei Y.; Pierce, Kate; Lally, Jake; Leaf, Elizabeth M.; Lin, Mu-En; Scatena, Marta; Giachelli, Cecilia M. (Frontiers in Cardiovascular Medicine, 2021)
Background: Calcific aortic valve disease is common in the aging population and is characterized by the histological changes of the aortic valves including extracellular matrix remodeling, osteochondrogenic differentiation, and calcification. Combined, these changes lead to aortic sclerosis, aortic stenosis (AS), and eventually to heart failure. Runt-related transcription factor 2 (Runx2) is a transcription factor highly expressed in the calcified aortic valves. However, its definitive role in the progression of calcific aortic valve disease (CAVD) has not been determined. In this study, we utilized constitutive and transient conditional knockout mouse models to assess the molecular, histological, and functional changes in the aortic valve due to Runx2 depletion. Methods: Lineage tracing studies were performed to determine the provenance of the cells giving rise to Runx2+ osteochondrogenic cells in the aortic valves of LDLr−/− mice. Hyperlipidemic mice with a constitutive or temporal depletion of Runx2 in the activated valvular interstitial cells (aVICs) and sinus wall cells were further investigated. Following feeding with a diabetogenic diet, the mice were examined for changes in gene expression, blood flow dynamics, calcification, and histology. Results: The aVICs and sinus wall cells gave rise to Runx2+ osteochondrogenic cells in diseased mouse aortic valves. The conditional depletion of Runx2 in the SM22α+ aVICs and sinus wall cells led to the decreased osteochondrogenic gene expression in diabetic LDLr−/− mice. The transient conditional depletion of Runx2 in the aVICs and sinus wall cells of LDLr−/−ApoB100 CAVD mice early in disease led to a significant reduction in the aortic peak velocity, mean velocity, and mean gradient, suggesting the causal role of Runx2 on the progression of AS. Finally, the leaflet hinge and sinus wall calcification were significantly decreased in the aortic valve following the conditional and temporal Runx2 depletion, but no significant effect on the valve cusp calcification or thickness was observed. Conclusions: In the aortic valve disease, Runx2 was expressed early and was required for the osteochondrogenic differentiation of the aVICs and sinus wall cells. The transient depletion of Runx2 in the aVICs and sinus wall cells in a mouse model of CAVD with a high prevalence of hemodynamic valve dysfunction led to an improved aortic valve function. Our studies also suggest that leaflet hinge and sinus wall calcification, even in the absence of significant leaflet cusp calcification, may be sufficient to cause significant valve dysfunctions in mice.